Optimization of the green synthesis of gold nanorods using aqueous extract of peeled sour guava as a source of antioxidants - M. Camila Patiño-González; Claudia E. Echeverri-Cuartas; Sandra Torijano-Gutiérrez; Sandra Milena Naranjo-Rios; Natalia A. Agudelo (PLoS ONE, 2025)
Obtaining gold nanorods (AuNRs) through biosynthesis is an alternative that replaces the traditional use of ascorbic acid with chemical compounds such as polyphenols, owing to their notable antioxidant properties. Therefore, we developed an AuNR biosynthesis method using an aqueous extract of sour guava (Psidium araca). Initially, a study was conducted to determine the antioxidant capacity of different parts of the fruit (pulp and peel) over 14 days. Four colorimetric techniques were used: total phenol, ABTS (2,2-azino-bis-3-ethylbenzothiazoline-6-sulphonic acid), FRAP (ferric reducing antioxidant power (FRAP), and DPPH (1,1-diphenyl-2-picrylhydrazyl). Subsequently, in stage 2, the selected aqueous extract was used, and two response surface designs were performed. The objective of this study was to find a model equation that would indicate the optimal parameters for obtaining AuNRs with a surface plasmon band at 808 nm, with possible applications in the health field. The results of the antioxidant capacity experiments were analyzed in Minitab® using a multilevel factorial design, and the peel exhibited the highest antioxidant capacity. Subsequently, the biosynthesis of AuNRs proceeded using a 5-factor response surface experimental design as input variables (concentration in mM of gold, silver, extract, NaBH4, and reaction time in hours) and longitudinal plasmon (LSPR) as output variables. The AuNRs were approximately 30 nm in size with an LSPR between 700 and 800 nm. Statistical model evaluation revealed a dependence between gold and time and gold–silver factors. Finally, antioxidant capacity was used to select the part (peel or pulp) of sour guava that could be used as a weak reducing agent. Moreover, the utility of surface-response methodology was explored to optimize the synthesis of AuNRs using green agents.